AB0252 Impact of age, disease-related factors, obesity and depression on lipid status and glycoregulation in patients with rheumatoid arthritis. (23rd January 2014) - Ostojic, P.; Bartolovic, D.; Cvijovic, A.; Ivanovic, B.; Damjanov, N.
Abstract : Background: The risk for cardiovascular disease is increased in rheumatoid arthritis (RA). Assessments based only on traditional risk factors are insufficient to capture the extent of cardiovascular risk in RA. Objectives: This study aims to estimate the impact of age, disease-related factors, obesity and depression on lipid status and glycoregulation in patients with RA. Methods: Thirty six patients with RA (30 women and 6 men), mean age 54.9 years and mean disease duration 7.9 years, were included in this study. We estimated the impact of age, disease duration, body mass index (BMI), disease activity (assessed by DAS28 index and CRP value), functional ability (measured by the HAQ disability index) and depression (assessed using the Beck's depression inventory - BDI) on glycoregulation and lipid status. Glycoregulation was assessed by measuring insulin resistance, insulin and glucose in the blood. Lipids tested in the blood included total cholesterol, HDL- and LDL- cholesterol and triglycerides. Results: BMI correlated significantly with total cholesterol (r=0.46, p=0.02), LDL-cholesterol (ρ=0.41, p=0.04) and triglycerides (ρ=0.65, p<0.001) in the blood. Obese (BMI≥30) and overweight patients (25<BMI<30) had higher triglyceride values (p<0.05) compared to patients with normal BMI (2.3 and 1.9 vs 1.1 mmol/l, respectively). Patients with high disease activity (DAS28 >5.1) had lower HDL-cholesterol values than patients with mild or moderate disease activity (1.68 vs 1.35 mmol/l, p=0.04). There was a statistically significant negative correlation between DAS28 index and HDL-cholesterol (ρ=-0.40, p=0.04). The BDI depression index correlated significantly with triglycerides in the blood (ρ=0.65, p=0.001). Patients on corticosteroid therapy had lower values of LDL-cholesterol and triglycerides, compared to patients without corticosteroids. Other factors assessed in this study (age, disease duration, CRP and HAQ index) did not have impact on the lipid status. We have noticed a significant correlation between CRP and insulin resistance (ρ=0.57, p=0.003), and insulin resistance with glycemia (ρ=0.59, p=0.002). Disease duration correlated also significantly with insulin resistance (ρ=0.44, p=0.04) and glycemia (ρ=0.50, p=0.01). Other factors assessed in this study (age, BMI, DAS28, HAQ index, depression and corticosteroids) did not have impact on glycoregulation. Conclusions: Longer disease duration and higher disease activity are associated with increased insulin resistance and low level of HDL-cholesterol in the blood. On the other hand, depression and obesity are associated with higher values of total cholesterol, LDL-cholesterol and triglycerides. To reduce the overall cardiovascular risk in patients with RA, not only disease activity should be treated, but also obesity and depression. Disclosure of Interest: None Declared